ANALISIS PENDAPATAN DAN KELAYAKAN USAHA KUE PIA PADA INDUSTRI RUMAH TANGGA KUE PIA RONY DI KOTA PALU - Tri Setyawan, Moh. Arief Eka; Muis, Abdul (AGROTEKBIS, 2018)
Indonesia known as the agricultural Nation,production agricultural products diverse, expected to support the economic growth at present and future. Necessary economic conditions balance between the field of the industry is supported by the agricultural tough. One commodity crops that are capable of supporting the establishment of several industries are green beans. Processing of green beans into the depths contents cake pia. Industry household Cake PIA Rony referred to one of the industry produce cake Pia is an example of the utilization of human resources to improve the income in home industry scale. The purpose of this study is to find out how much revenues and the level of the feasibility on the cake Pia industry household Cake PIA Rony in City. This research has been carried out in the industry household Cake PIA Rony at Jalan zebra 5 Number 1 District of South Palu,Palu city from March to April 2016. Determination of respondents using purpossive. Data used the form of data primary and secondary. Analysis of data that is used is income analysis and feasibility analysis revenue cost ratio. The results shows that revenues of Pia industry household Cake PIA Rony in the Palu Cityis Rp.6,783,889 per month. Industry household Cake PIA Rony in the Cityof Paluis feasible with the value of R/C of 1.30. Keywords: Cake Pia, Feasibility, Income.